How long do teacher effects persist? - Spyros Konstantopoulos (Institute for the Study of Labor (IZA), 2007)
Previous findings from experimental and non-experimental studies have demonstrated that teachers differ in their effectiveness. In addition, evidence from non-experimental studies has indicated that teacher effects can last up to five years. This study used high-quality data from a four-year randomized experiment in which teachers and students were randomly assigned to classes to examine whether teacher effects on student achievement persist over time. Teacher effects are defined as teacher specific residuals adjusted for student and treatment effects. Findings indicate that the teacher effects are cumulative and observed not only in the current or the following grade, but they endure up to three years in early elementary grades. The findings also suggest that teacher effects are important and their additive effects on student achievement are as large as the additive effects of small classes. Finally, teacher effects are larger in reading than in mathematics.
Keywords: 330; Bildungsniveau; Schüler; Lehrkräfte; Test; USA